Detection of cell‐free DNA fragmentation and copy number alterations in cerebrospinal fluid from glioma patients. Issue 12 (6th November 2018) - Mouliere, Florent; Mair, Richard; Chandrananda, Dineika; Marass, Francesco; Smith, Christopher G; Su, Jing; Morris, James; Watts, Colin; Brindle, Kevin M; Rosenfeld, Nitzan
Abstract: Glioma is difficult to detect or characterize using current liquid biopsy approaches. Detection of cell‐free tumor DNA (cftDNA) in cerebrospinal fluid (CSF) has been proposed as an alternative to detection in plasma. We used shallow whole‐genome sequencing (sWGS, at a coverage of < 0.4×) of cell‐free DNA from the CSF of 13 patients with primary glioma to determine somatic copy number alterations and DNA fragmentation patterns. This allowed us to determine the presence of cftDNA in CSF without any prior knowledge of point mutations present in the tumor. We also showed that the fragmentation pattern of cell‐free DNA in CSF is different from that in plasma. This low‐cost screening method provides information on the tumor genome and can be used to target those patients with high levels of cftDNA for further larger‐scale sequencing, such as by whole‐exome and whole‐genome sequencing. Synopsis: Gliomas are challenging to detect based on cell‐free tumor DNA (cftDNA) in body fluids. In this study, a combined analysis of somatic copy number alterations (SCNA) and DNA fragmentation patterns based on shallow whole genome sequencing (sWGS) improves cftDNA detection in cerebrospinal fluid (CSF). SCNAs were detected by sWGS in CSF from 5 out of 13 patients. Cell‐free DNA fragments are shorter in CSF than in plasma, with > 50% of fragments below 150 bp. CSF cell‐free DNA fragment length distributions showed 10‐bp periodic peaks, which were decreased in samples where SCNAs were detected. SCNAs and DNA fragmentation patterns in sWGS data can enhance tumour detection using CSF samples. Abstract : Gliomas are challenging to detect based on cell‐free tumor DNA (cftDNA) in body fluids. In this study, a combined analysis of somatic copy number alterations (SCNA) and DNA fragmentation patterns based on shallow whole genome sequencing (sWGS) improves cftDNA detection in cerebrospinal fluid (CSF).